2014
DOI: 10.1016/j.gendis.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Urine-derived stem cells: A novel and versatile progenitor source for cell-based therapy and regenerative medicine

Abstract: Engineered functional organs or tissues, created with autologous somatic cells and seeded on biodegradable or hydrogel scaffolds, have been developed for use in individuals with tissue damage suffered from congenital disorders, infection, irradiation, or cancer. However, in those patients, abnormal cells obtained by biopsy from the compromised tissue could potentially contaminate the engineered tissues. Thus, an alternative cell source for construction of the neo-organ or functional recovery of the injured or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
121
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 68 publications
0
121
1
3
Order By: Relevance
“…Prior studies have shown that USCs, similar to iMSCs, have a fast, stable expansion speed and maintain telomere length and high telomerase activity [36,37]. Therefore, USCs may represent a virtually unlimited supply of autologous cells that may be used for cell therapy in rodent models or clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that USCs, similar to iMSCs, have a fast, stable expansion speed and maintain telomere length and high telomerase activity [36,37]. Therefore, USCs may represent a virtually unlimited supply of autologous cells that may be used for cell therapy in rodent models or clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include fibroblasts isolated from skin biopsies or stem cells isolated from urine (most likely of glomerular parietal epithelial origin) [32–34]. As a result, both patients and healthy controls tend to be willing to donate cells for banking to be used for diagnostic and research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that stem cells can secrete paracrine factors to help the resident cells to survival and perform normal function as well as regulate the local micro‐environment (Jeon et al, ; Liang, Ding, Zhang, Tse, & Lian, ). Recently, it has been reported that urine‐derived stem cells (USCs) is also a stem cell candidate for tissue regeneration as it has the characters of stem cells (Bodin et al, ; Zhang, Wei, Li, Zhou, & Zhang, ). It was reported that USCs were positive for CD29, CD44, CD73, and CD90 antigen, and negative for CD31, CD34, CD45, CD133, CD309, and HLA‐DR.…”
Section: Introductionmentioning
confidence: 99%